Optimalisasi Biaya Transportasi Produk UMKM Naturies Indonesia Dengan Metode Northwest Corner Dan Vogel’s Approximation - Yuliana Yuliana; Tasari Tasari; Anita Setiyaningsih; Fika Aisyah Munif; Miftacha Febriani Putri (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2022)
Naturies Indonesia is one of the UMKM for spice drinks in Macanan, Klaten, Central Java which is developing. As one of the growing UMKM, Naturies Indonesia is experiencing problems related to the distribution of its products. Naturies Indonesia has incurred transportation costs of Rp.442,100.00 per week in distributing its products to 5 distributors (Kudus, Jakarta, Shopee, Bandung, and offline). Due to human resource constraints, Naturies Indonesia does not yet have a thorough plan to reduce shipping costs in allocating products from production sites to customers or distributors. Through this applied research, this research aims to find the optimization of product delivery costs. Data were collected through interviews and documentation, then analyzed using the Northwest Corner and Vogel's Approximation methods. Analysis using the Northwest Corner method found a shipping cost of IDR 431,600.00, while the Vogel's Approximation method found a shipping cost of IDR 427,900.00. The shipping costs found were actually lower than the financing that had been issued so far.  Keyword: northwest cor, spice drinks, optimization of transportation, UMKM Naturies Indonesia, vogel’s approximation